Recopilación de técnicas ancestrales artesanales con potencial de innovación en sector textil, confección, diseño y moda en el departamento de córdoba Colombia. - Guzmán Martínez, Karina del Carmen
In the department of Córdoba there are companies, fashion designers and production units with unsatisfied needs, particularly in the offer of specialized services that complement some activities within their production processes, which make a difference and give added value to their products. Artisanal inputs, typical of the region, are a differential component that would cover these current needs, framed in national policies to support local development and the dynamization of the orange economy that supports creative and cultural industries. Therefore, it is necessary to develop activities that contribute to strengthening and preserving the ancestral artisan techniques of the department of Córdoba through inputs and / or accessories that enrich the textile, clothing, design and fashion sector.   The above is possible through a process that allows investigating and consolidating the information related to the ancestral artisan techniques of the department of Córdoba, identifying the Heritage of the Zenú and Embera Katio Cultures, which would lead to visualizing the wide cultural material wealth that it has the department of Córdoba, which could be used in the textile, clothing, design and fashion sectors through quality supplies and / or accessories, made by artisans of the department, thus boosting their family economy, contributing to the use of the cultural wealth in the framework of the orange economy and exalting and promoting the cultural identity of Cordoba.